ЕКОЛОГІЧНА КРИЗА: ПРИЧИНА ТА НАСЛІДОК КРИЗИ ДУХОВНОСТІ. - ТАГЛІНА, Ю. С. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
У статті розглядаються питання, що стосуються екологічної етики. Особливаувага приділяється питанню: чи є екологічна криза причиною кризи духовності людини,або є її наслідком? З точки зору автора, коріння зростання екологічної кризи требашукати у відсутності стабільної духовної основи в сучасному житті людини.Особистість, яка вступає в діалог з природою, має бути внутрішньо вільна і здатнанести відповідальність за свої вчинки, дотримуючись не споживчих, а аксіологічнихпріоритетів у взаємодії з навколишнім світом.Таглина Ю.С. ЭКОЛОГИЧЕСКИЙ КРИЗИС: ПРИЧИНА И СЛЕДСТВИЕКРИЗИСА ДУХОВНОСТИ В статье рассматриваются вопросы, касающиесяэкологической этики. Особое внимание уделяется вопросу: является экологический кризиспричиной кризиса духовности человека, либо является ее следствием? С точки зренияавтора, корни экологического кризиса нужно искать в отсутствии стабильной духовнойосновы в современной жизни человека. Личность, которая вступает в диалог с природой,должна быть внутренне свободна и способна нести ответственность за свои поступки,придерживаясь не потребительских, а аксиологических приоритетов во взаимодействиис окружающим миром.Ключевые слова: кризис духовности, экологическая этика, экологический кризис,техногенное обществоTaglina J.S. ECOLOGICAL CRISIS: CAUSE AND CONSEQUENCE OF THESPIRITUAL CRISIS The article describes question environmental ethics. Special attention ispaid to the question: is the environmental crisis caused crisis of human spirituality, or is itseffect? From the point of view of the author cause of the problem of the environmental crisismust be sought in the absence of a stable spiritual foundation in modern life.The person who enters into a dialogue with nature, must be inwardly free, and can beresponsible for their actions, not adhering to the consumer, but adhering axiological priorities incollaboration with the world.Elements of ecological culture in general should be formed and detected in differentareas of society: economic, social, political, spiritual, moral. Indeed, environmentalconsciousness is an important step to understanding what way can be harmonized relationshipbetween humanity and the natural environment.Freedom of personality involves understanding these alternatives requires capabilitiesand abilities to work for the implementation of the selected alternative. In technogenic society,this problem is particularly acute, and therefore need to seek ways and means of protectingfreedom of each individual, which is closely intertwined with the problem of the prospects oftechnological society.Prospects for overcoming the ecological crisis will depend on those real mechanisms toprotect individual freedom, which can create a technogenic society.Keywords: spiritual crisis, environmental ethics, ecological crisis, technogenic society.